Is There an Equivalence between Measures of Landscape Structural and Functional Connectivity for Plants in Conservation Assessments of the Cerrado? - Thais Martins Issii; Erico Fernando Lopes Pereira-Silva; Carlos Tomás López de Pablo; Rozely Ferreira dos Santos; Elisa Hardt (Land, 2020)
Landscape connectivity can be assessed based on the physical connection (structural connectivity) or the maintenance of flow among habitats depending on the species (functional connectivity). The lack of empirical data on the dispersal capacity of species can lead to the use of simple structural measures. Comparisons between these approaches can improve decision-making processes for the conservation or restoration of habitats in fragmented landscapes, such as the Cerrado biome. This study aimed to understand the correspondence between the measures of landscape structural and functional connectivity for Cerrado plants. Three landscapes with cerradão patches in a pasture matrix were selected for the application of these metrics based on the functional connectivity of four profiles of plant dispersal capacity. The results showed divergent interpretations between the measures of landscape structural and functional connectivity, indicating that the assessment of biodiversity conservation and landscape connectivity is dependent on the set of metrics chosen. Structurally, the studied landscapes had the same number of cerradão patches but varied in optimal resource availability, isolation, heterogeneity, and aggregation. Functional connectivity was low for all profiles (based on the integral index of connectivity—IIC) and null for species with a low dispersal capacity (based on the connectance index—CONNECT), indicating that species with a medium- to long-distance dispersal capacity may be less affected by the history of losses and fragmentation of the Cerrado in the pasture matrix. The functional connectivity metrics used allowed a more robust analysis and, apparently, better reflected reality, but the lack of empirical data on dispersal capacity and the difficulty in choosing an indicator organism can limit their use in the management and planning of conservation and restoration areas.